Pengaruh Teman Sebaya Dan Lingkungan Belajar Terhadap Prestasi Belajar Siswa Kelas IX DI SMP Negeri 6 Pematang Siantar Tahun Ajaran 2023/2024 - Vincen Yakob Purba; Debbi Petra Meyana Sitorus; Paulina Herlina N Sirait (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This study aims to obtain knowledge about the influence of peers and the environment on the learning achievement of grade IX students of SMP Negeri 6 Pematang Siantar for the 2023/2024 school year. This type of research is qualitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 24. The total population in this study was 223, and the sample used was 142 people. The sampling technique used is simple random sampling. The data collection technique used is a questionnaire (questionnaire). The hypothesis data collection technique uses multiple regression analysis and coefficient of determination (R2).